A review of the genus Smicronyx Schoenherr (Coleoptera, Curculionidae, Curculioninae) in tropical Africa - Haran, Julien (Zootaxa, 2018)
The genus Smicronyx Schoenherr (Curculionidae, Curculioninae, Smicronychini) contains several species considered as potential biocontrol agents of parasitic and hemi-parasitic plants of crops (Striga spp. (Orobanchaceae) and Cuscuta spp. (Convolvulaceae)). However, the diversity of species occurring in Africa has not been explored in detail. This study reviews the species of Smicronyx occurring in continental tropical Africa. In total, 16 species are recorded for this region: 6 species previously described (S. bisignatus Hoffmann, S. gossypii Marshall, S. guineanus Voss, S. kiboanus Voss, S. pauperculus Wollaston and S. remaudierei Hoffmann), 2 newly recorded for the area (S. albosquamosus Wollaston, S. syriacus Faust), and 8 species are described as new (S. adjamati sp. n., S. crassithorax sp. n., S. kenyanus sp. n., S. namibicus sp. n., S. rufus sp. n., S. buchnerae sp. n., S. zambianus sp. n., S. zonatus sp. n.). A key to the species and photographs of the habitus and male genitalia are provided.